REFORMASI MANAJEMEN ADMINISTRASI PENDIDIKAN ISLAM DI ERA TATA KELOLA DIGITAL - M. Amrullah azis; Indi Supriyadi (Eduvis : Jurnal Manajemen Pendidikan Islam, 2023)
The rapid acceleration of digital transformation across public service sectors has created an urgent imperative for Islamic educational institutions to fundamentally reform their administrative management systems. Despite growing policy pressure and technological availability, the majority of Islamic educational institutions in Indonesia continue to operate within bureaucratic administrative paradigms that are largely incompatible with the efficiency, transparency, and accountability demands of digital governance. This study investigates the reform of administrative management in Islamic educational institutions within the context of digital governance, pursuing three objectives: (1) to analyze the conceptual foundations of administrative management reform in Islamic education, (2) to identify principal barriers to digital governance adoption in Islamic educational institutions, and (3) to construct a model of digital administrative governance that is both technologically progressive and rooted in Islamic values of amanah, adl, and shura. Employing a systematic library research methodology with thirty-three sources published between 2020 and 2025, the study proposes the Islamic Digital Governance Framework (IDGF), a five-pillar model integrating digital transformation principles with Islamic administrative ethics. Implications for madrasah administrators, educational technology policymakers, and Islamic educational governance scholars are elaborated.